Lymphopenia at 4 Days Postoperatively Is the Most Significant Laboratory Marker for Early Detection of Surgical Site Infection Following Posterior Lumbar Instrumentation Surgery - Iwata, Eiichiro (Asian Spine J, 2016)
STUDY DESIGN: Case control study. PURPOSE: To identify the most significant laboratory marker for early detection of surgical site infection (SSI) using multiple logistic regression analysis. OVERVIEW OF LITERATURE: SSI is a serious complication of spinal instrumentation surgery. Early diagnosis and treatment are crucial. METHODS: We retrospectively reviewed the laboratory data of patients who underwent posterior lumbar instrumentation surgery for degenerative spinal disease from January 2003 to December 2014. Six laboratory markers for early SSI detection were considered: renewed elevation of the white blood cell count, higher at 7 than 4 days postoperatively; renewed elevation of the C-reactive protein (CRP) level, higher at 7 than 4 days postoperatively; CRP level of >10 mg/dL at 4 days postoperatively; neutrophil percentage of >75% at 4 days postoperatively; lymphocyte percentage of <10% at 4 days postoperatively; and lymphocyte count of <1,000/µL at 4 days postoperatively. RESULTS: Ninety patients were enrolled; five developed deep SSI. Multivariate regression analysis showed that a lymphocyte count of <1,000/µL at 4 days postoperatively was the sole significant independent laboratory marker for early detection of SSI (p=0.037; odds ratio, 11.9; 95% confidence interval, 1.2–122.7). CONCLUSIONS: A lymphocyte count of <1,000/µL at 4 days postoperatively is the most significant laboratory marker for early detection of SSI.